Filtração eletroquímica com nanotubos de carbono como tecnologia alternativa à degradação de estrogênios e remoção da atividade estrogênica - Cunha, Gustavo dos Santos (2019)
Estrogens are biologically active micro-pollutants, difficult to degrade and can interfere with the functioning of the endocrine and reproductive system of animals and humans. Carbon nanotube electrochemical filtration is a novel technology that combines electro-oxidation and electrosorption to remove contaminants in water. The aim of this work is to analyze the performance of an electrochemical filter using carbon nanotubes (NC) as anode for the degradation of 37 µM of 17β-estradiol (E2) and 17αethinylestradiol (EE2) and removal of the estrogenic activity. Different total voltages (0 - 2.5 V) were applied in two aqueous matrices (ultrapure water and domestic effluent), under volumetric flow rate of 1.5 mL.min-1 and with 10 mM sodium sulfate (Na2SO4) as electrolyte support. Results showed an estrogen removal up to 99.1% in ultrapure water and 96.3% in domestic effluent under 2.5 V. However, estrogen activity was not completelly removed, which is confirmed by the remaining concentration of the estrogens.